Efeito do inoculante Al-Nb-B na microestrutura e propriedades mecânicas da liga AA2017 fabricada por fusão em leito de pó a laser - dos Santos Bomfim, Pamela Karina (2023)
The blending of finer powders of Ti, Zr, Ta, Sc, and Nb compounds as inoculants has been a promising strategy to modify precipitation-hardened aluminum alloys for laser-based powder bed fusion process (L-PBF), promoting a crack-free equiaxed microstructure in the final L-PBF component. Despite this, manipulating nanoparticles may bring risks to the operator's health, and such particles tend to agglomerate, making it difficult to obtain a perfect mixture. Therefore, this doctoral thesis aimed to investigate the effect of mixing micrometric particles of the inoculant Al-5.0Nb-0.5B in the AA2017 alloy on the microstructural evolution, as well as in the mechanical behavior. Two additions were studied: AA2017+ 1% Al-5.0Nb-B and AA2017+2%Al-5.0Nb-0.5B (%wt). Through the physical characterizations and the evaluation of the rheological properties, it was observed that the mixed powder particles did not show high sphericity; they were also slightly more agglomerated, thus presenting more significant flow difficulties in most of the rheological tests. Initially, the processing window for the AA2017 alloy was determined and, based on these results, AA2017+2%Al-5.0Nb-0.5B alloy was produced by L-PBF. It has been found that the AA2017 sample had columnar aluminum grains with cracks crossing the melt pools, while AA 2017+2% Al-5.0Nb-0.5B consisted of equiaxed grains. EBSD results for both samples indicated a low fibre texture; however, the AA2017 sample with inoculant showed a texture whose intensity was slightly lower. Finally, the compression properties were measured, and it was noted that the yield strength of the AA2017+2%Al-Nb-B alloy (~215 MPa) was higher than the AA2017 (~171 MPa).